2022
DOI: 10.1007/s10072-022-05963-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular autonomic nervous system responses and orthostatic intolerance in astronauts and their relevance in daily medicine

Abstract: Background The harsh environmental conditions during space travel, particularly weightlessness, impose a major burden on the human body including the cardiovascular system. Given its importance in adjusting the cardiovascular system to environmental challenges, the autonomic nervous system has been in the focus of scientists and clinicians involved in human space flight. This review provides an overview on human autonomic research under real and simulated space conditions with a focus on orthosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…Neurally mediated syncope is a common reason for emergency room admissions [ 28 ], but can also occur in astronauts returning from space [ 19 ]. On Earth, the condition is relatively benign except for fall-related injuries, yet affected patients may experience a strong negative impact on quality of life [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neurally mediated syncope is a common reason for emergency room admissions [ 28 ], but can also occur in astronauts returning from space [ 19 ]. On Earth, the condition is relatively benign except for fall-related injuries, yet affected patients may experience a strong negative impact on quality of life [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data on sympathetic nervous activity during space flight are contrasting and may be related to mission duration as well as inter-individual variability in the susceptibility to the space environment 36 . Several studies demonstrated that plasma and urine catecholamine levels do not change during long-term space flight 37 , 38 .…”
Section: Volume Regulationmentioning
confidence: 99%
“…In the present study, orthostatic tolerance decreased more than 5 min less in both intervention groups compared with the control group. Similarly, daily artificial gravity training elicited through short-arm centrifugation had a beneficial effect on orthostatic tolerance in previous studies, which applied different artificial gravity training protocols [ 32 ].…”
Section: Discussionmentioning
confidence: 92%